Pengaruh Literasi Keuangan, E-Money, dan Gaya Hidup terhadap Perilaku Keuangan Mahasiswa Akuntansi pada Cashless Society - Liziyannida Liziyannida; Suwandi Suwandi (Jurnal Kendali Akuntansi, 2026)
This study aims to analyze the influence of financial literacy, e-money use, and lifestyle on the financial behavior of accounting students in the context of a cashless society. The research population includes students of the accounting study program of the Faculty of Economics and Business, University of Muhammadiyah Gresik, Semen Indonesia International University, and Gresik University. The sampling technique used accidental sampling with a total of 120 respondents in the 6th semester. Primary data was obtained through the distribution of questionnaires, then analyzed using quantitative methods with the help of SmartPLS software. The results of the study show that financial literacy does not have a significant effect on students' financial behavior. Conversely, the e-money variable has a significant positive influence on financial behavior, indicating that the use of digital transactions encourages more practical financial management patterns. In addition, lifestyle has also been shown to have a significant positive effect on financial behavior, indicating that students' consumption preferences and lifestyle also determine how they manage their finances in the cashless era. This research makes an empirical contribution in understanding the factors that influence the financial behavior of the younger generation, as well as being the basis for the development of financial literacy and policies related to digital payment systems in the higher education environment.